Radiation-free flexible ureteroscopy for kidney stone treatment. Issue 3 (3rd July 2019) - Manzo, Braulio O.; Lozada, Edgard; Manzo, Gildardo; Sánchez, Héctor M.; Gomez, Francisco; Figueroa, Alejandro; Gonzalez, Adrian
ABSTRACT: Objectives : To evaluate the safety and effectiveness of flexible ureterorenoscopy (fURS) with holmium laser lithotripsy for treating kidney stones without fluoroscopy as method of best practice for patients and endourologists. Patients and Methods : All patients treated for kidney stones by fURS with holmium laser lithotripsy from February 2016 to February 2017 were retrospectively evaluated. The patients' demographic characteristics, stone features (size, number, and location), surgical variables (use of fluoroscopy, operative and fluoroscopy time), complications, and success rate (employing stone-free rate [SFR]), were included in the analysis. Results : In all, 100 patients met the inclusion criteria: 33 fURS were performed under fluoroscopy (Group 1) and 67 without it (Group 2). The mean operating time was 94.33 vs 98.29 min ( P = 0.888), respectively. The mean stone volume was 78.5 vs 82.4 mL ( P = 0.885), respectively. The SFR was 63.6% and 64.2% ( P = 0.771), the perioperative complications rate was 18.2% vs 11.9% ( P = 0.285), and the postoperative complications rate was 24.2% and 10.4%, in groups 1 and 2 respectively ( P = 0.174). Conclusions : fURS with holmium laser lithotripsy without fluoroscopy was a feasible and safe treatment for kidney stones. There was no difference between the use of fluoroscopy or not regarding complications or SFR. Thus, we can reduce the risks of radiation exposure to patients and medical staff whilst maintaining surgical success. However, multicentre randomised controlled studies are necessary to evaluate fluoroless URS further and to confirm our present results. Abbreviations: PTFE: polytetrafluoroethylene; SFR: stone-free rate; (f)URS: (flexible) ureterorenoscopy/ureterorenoscopies; US: ultrasonography